(untitled) (Tanzania Journal for Population studies and Development, 2015)
Rapid urbanization and inadequate capability to cope with the housing needs of urban populations have contributed to the development of hazardous settlements in urban areas. This study examines the patterns of growth of hazardous settlements in Iringa, Tanzania, the associated risks and their implications. Due to the complexity of the problem, the study employed mixed research approaches in data collection and analysis, including documentary review, interviews and questionnaires, focus group discussions, field observations and photography. The findings revealed that residents of age group of between 18 and 44 years were the majority in hazardous settlements, and the majority of household heads were married females. Factors contributing to people to reside in hazardous settlements include failure to get surveyed plots, proximity to work places, business opportunities, clashes with landlords, and chances to get free plots. Hygienic risks were cited to be the main problems facing residents in hazardous settlements. Other problems were inadequate social services, environmental risks, crimes, fear from forceful evictions and urban poverty. To resolve the problems associated with hazardous settlements, the study recommends, among others, that the government reviews urban planning policies, plans and standards; and that urban authorities should collaborate with utility service institutions to plan and institutionalize policies for urban settlements.